Case Report: Three cases of lung large cell neuroendocrine carcinoma with clinicopathological features of SMARCA4 (BRG1) deficiency - Zou, Fangfang; Jia, Jingdan; Wang, Yizeng; Fei, Xiaochun; Wang, Chaofu; Chen, Xiaoyan (Frontiers in Oncology, 2025)
ObjectiveTo investigate the clinicopathological characteristics, differential diagnosis and potential therapeutic targets of SMARCA4-deficient large cell neuroendocrine carcinoma (SD-LCNEC) in the lung.MethodsWe analyzed the clinicopathological features of 3 cases of SD-LCNEC and reviewed relevant literature. Differential diagnoses were conducted using a panel of immunohistochemical antibodies.ResultsThe patients, aged 57 to 73 years, had tumors located in the right upper lobe, left hilum, and left upper lobe of the lung, respectively. All patients presented with lung masses. The tumors exhibited neuroendocrine carcinoma morphology, characterized by large tumor cells (nuclear diameter >3 lymphocytes), frequent mitoses, and prominent nucleoli. Tumor cells tested negative for SMARCA4 but were positive for Chromogranin-A(CgA), Synaptophysin (SYN), Insm-1, TTF-1 (partial), and Ki67 (90%). They were also negative for NapsinA, P63, P40, CK5/6, CK7, and NUT. Postoperative follow-up revealed one death, one case of Progressive Disease (PD), and one case of Stable Disease (SD).ConclusionSD-LCNEC is a rare and clinically aggressive carcinoma, often presenting with lymph node metastasis at the initial stage. Its morphology is equivalent to LCNEC; however, immunohistochemical staining indicates the absence of SMARCA4 and a reduction in neuroendocrine markers and TTF-1. There is no standardized treatment, but SMARCA4 may serve as a potential therapeutic target. Accurate identification of the molecular subtype of SD-LCNEC is crucial.